Philippines : Financial Soundness Indicators. (IMF Staff Country Reports; Country Report ;, 2021)
With the support of the IMF's Asia and Pacific Department (APD) and the Bangko Sentral ng Pilipinas (BSP), an IMF Statistics Department (STA)'s remote financial soundness indicators (FSIs) technical assistance (TA) mission took place during April 30-May 14, 2021. The main objective of the mission was to assist the BSP in compiling FSI for the other financial corporations (OFCs) sector, in line with the 2019 Financial Soundness Indicators Compilation Guide (Guide). Specifically, the Guide recommends compiling indicators for money market funds, insurance corporations, and pension funds, as well as for the total OFC sector. The work of the mission was facilitated by the excellent collaboration of BSP's staff, in particular of the Department of Economic Statistics (DES). The list of officials met during the mission can be found in Appendix I.